POTENTIAL NATIONAL SPATIAL DATA INFRASTRUCTURE (NSDI) AND VOLUNTEREED GEOGRAPHIC INFORMATION (VGI) INTEGRATION TO ACHIEVE SEAMLESS-UPDATING-RELIABLE SPATIAL PLANNING INFORMATION FROM NATIONAL THROUGH LOCAL GOVERNANCE LEVEL IN INDONESIA - Yudono, Adipandang (Badan Informasi Geospasial in Partnership with MAPIN, 2015)
This paper focuses on the role of National Spatial Data Infrastructure (NSDI) in relation to spatial planning formulation in Indonesia. The reason for selecting this topic is the fragmented manner of spatial data distribution amongst the Indonesian government institutions responsible for spatial planning at present. Thus, spatial planning conflicts at different levels (e.g. province and municipality) or at similar levels (e.g. regency or municipality) often occur. Furthermore, a lack of spatial data management in spatial planning has led to the state spending considerable sums each year to produce, process and use geographic data. Moreover, owing to a rather convoluted bureaucracy, crossjurisdictional organisational circumstances have added a delicate political situation to accessing spatial data. Hence, this research considers the issue of moving towards a consensus on sharing fundamental geospatial datasets to meet the public interest and geospatial standardization to achieve the geospatial information integration amongst government institutions and private agencies in national geospatial information provider. In addition, a traditional NSDI application using top-down approach has raised several issues, for instance lack of up-to-date geospatial information. Which is this issue may overcome by engaging bottom-up Volunteered Geographic Information (VGI) approach. Practically, most of NSDI scholars have limited understanding to what extent NSDI may accommodate a bottom-up VGI in terms of national/state spatial data management. Therefore, to fill knowledge gap, this study will finding out the possibility NSDI in accommodating VGI process and mechanism pertain national spatial data management and support accelerating geospatial information implementation for spatial planning purposes.Keywords: NSDI, Spatial planning, VGI, Geospatial InformationABSTRAKMakalah ini berfokus pada peran Infrastruktur Data Spasial Nasional (IDSN) dalam kaitannya dengan perumusan perencanaan tata ruang di Indonesia. Alasan untuk memilih topik ini adalah cara distribusi data spasial yang terfragmentasi di antara lembaga-lembaga pemerintah Indonesia yang bertanggung jawab untuk perencanaan tata ruang saat ini. Dengan demikian, konflik perencanaan tata ruang pada tingkat yang berbeda (misalnya provinsi dan kabupaten) atau pada tingkat yang sama (misalnya kabupaten atau kota) sering terjadi. Selain itu, kurangnya manajemen data spasial dalam perencanaan tata ruang telah menyebabkan pengeluaran negara dalam jumlah yang cukup besar setiap tahun untuk memproduksi, memproses dan menggunakan data geografis. Selain itu, karena birokrasi yang agak berbelit-belit, keadaan organisasi lintas yurisdiksi telah menambahkan secara halus situasi politik untuk mengakses data spasial. Oleh karena itu, penelitian ini menganggap isu bergerak menuju konsensus tentang berbagi dataset geospasial dasar untuk memenuhi kepentingan publik dan standarisasi geospasial untuk mencapai integrasi informasi geospasial di antara lembaga-lembaga pemerintah dan lembaga swasta dalam penyediaan informasi geospasial nasional. Selain itu, aplikasi tradisional IDSN menggunakan pendekatan top-down telah mengangkat beberapa isu, misalnya kurangnya informasi geospasial yang up-to-date. Yang merupakan masalah ini dapat diatasi dengan pendekatan Volunteered Geographic Information (VGI) secara bottom-up. Secara praktis, sebagian besar ahli IDSN memiliki pemahaman yang terbatas sejauh mana IDSN dapat mengakomodasi pendekatan bottom-up VGI dalam hal pengelolaan data spasial nasional. Oleh karena itu, untuk mengisi kesenjangan pengetahuan ini, penelitian ini akan mencari tahu kemungkinan IDSN dalam mengakomodasi proses VGI dan mekanisme yang berhubungan dengan pengelolaan data spasial nasional dan dukungan percepatan implementasi informasi geospasial untuk tujuan perencanaan tata ruang.Kata kunci: IDSN, perencanaan Tata Ruang, VGI, Informasi Geospasial